MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM PRAKTIK WUDHU DI SMP NEGERI 4 BANDAR BARU PIDIE JAYA - Izaryani (Journal of Contemporary Indonesian Islam, 2024)
The right model will determine the achievement of the quality of learning. The use of practical, effective and fun models will be able to foster student activity in teaching and learning activities. Therefore, this study aims: To describe what are the learning models of Islamic religious education in the practice of ablution at SMPN 4 Bandar Baro Pidie Jaya. Qualitative research method, descriptive approach. Data collection techniques through interviews, observation and documentation. The results showed that: The learning models used by Islamic Religious Education teachers in the practice of ablution include discovery learning with a scientific approach, problem-based learning, contextual teaching and learning, laboratory-based learning models, and demonstration methods.